The influence of birth season on mortality in the United States. Issue 5 (21st March 2016) - Sohn, Kitae
Abstract : Objectives: Birth season is related to a variety of later outcomes. Among them, mortality is of great interest because it represents lifetime health outcomes. We examined the relationship between birth season and mortality in the US. Methods: We merged the US National Health Interview Survey (NHIS) and NHIS public‐use linked mortality files and analyzed 17, 082 men and 19, 075 women who were followed for 20 years from 1986 to 2006. We used the Cox proportional hazards model to relate birth quarter to mortality, controlling for birth year fixed effects. Results: After controlling for years of schooling and birth year fixed effects, we found that, relative to men born in the first quarter, men born in the fourth quarter were 11% less likely to die. For women, the benefit was the largest for women born in the third quarter who were 14% less likely to die than women born in the first quarter. In the relationship between birth season and mortality, cardiovascular diseases played a noticeable role for men and malignant neoplasms for women. Conclusions: These results were consistent with those for some developed countries, but not entirely with those for contemporary developing countries and developed countries of the past. Simple mechanisms based on the perinatal environment cannot account for the inconsistent results. We suggest that family background may play some, but not an exhaustive, role in the relationship between birth season and mortality. Am. J. Hum. Biol. 28:662–670, 2016. © 2016 Wiley Periodicals, Inc.